2018
DOI: 10.1002/tox.22557
|View full text |Cite
|
Sign up to set email alerts
|

Butylidenephthalide abrogates the myofibroblasts activation and mesenchymal transdifferentiation in oral submucous fibrosis

Abstract: Oral submucous fibrosis (OSF) is a premalignant disorder in the oral cavity, and areca nut chewing habit has been implicated in the persistent activation of myofibroblasts and the subsequent fibrosis. Therefore, it is critical to ameliorate the excessive activities of myofibroblasts prior to the malignant transformation of OSF. In the current study, we evaluated the cytotoxicity of butylidenephthalide (BP), a major phthalide ingredient of Angelica sinensis, in fibrotic buccal mucosal fibroblasts (fBMFs) as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Cell movement toward the center of the wound area was photographed at 0 and 48 hours under a microscope. Cell movement into the wound area will be photographed at 0 and 24 hours under a microscope …”
Section: Methodsmentioning
confidence: 99%
“…Cell movement toward the center of the wound area was photographed at 0 and 48 hours under a microscope. Cell movement into the wound area will be photographed at 0 and 24 hours under a microscope …”
Section: Methodsmentioning
confidence: 99%
“…Over the past few years, growing attention has been paid to the use of natural products against a variety of diseases, including fibrosis and cancers [20,21]. Our group has also demonstrated the effect of various natural compounds on the suppression of oral cancer or OSF via the reduction of inflammation or mesenchymal transdifferentiation [22,23,24,25]. Current evidence has suggested that TGF-β signaling is the key pathway to trigger the manifestation of OSF [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…EMT-inducing transcription factors such as snail, slug, and twist are involved in the pathogenesis of betel nut related OSF. They initiate and facilitate the acquisition of a mesenchymal phenotype by repressing E-cadherin [27,73,75]. Zinc finger E-box binding homeobox 1 (ZEB1), another EMT-inducing transcription factor, is also implicated in betel nut associated OSF pathogenesis because it activates the α-SMA promoter [74].…”
Section: Epithelial Mesenchymal Transitionmentioning
confidence: 99%
“…It has demonstrated therapeutic efficacy against OSF. In vitro tests revealed that butylidenephthalide downregulates α-SMA, fibronectin, and type 1 collagen A1 and reduces myofibroblast bioactivity [75]. Glabridin is derived from the root of Glycyrrhiza glabra (licorice).…”
Section: Natural Compound Remediesmentioning
confidence: 99%
See 1 more Smart Citation